Intraocular Pressure Changes During Oral Glucose Tolerance Tests in Diabetic and Non-diabetic Individuals - Yildiz, P.; Kebapci, M. N.; Mutlu, F.; Yasar, S.; Gürsoy, H.; Yildirim, N. (Experimental and Clinical Endocrinology & Diabetes, 2016)
Background: Hyperglycaemia in diabetic patients may lead to elevated intraocular pressure. Different reasons have been suggested in previous studies to explain the increase in intraocular pressure. The purpose of the present study was to investigate the change in intraocular pressure during oral glucose tolerance tests in diabetic and non-diabetic subjects.Patients and Methods: 51 individuals who fulfilled the inclusion criteria of the study and were scheduled for oral glucose tolerances tests based on the recommendations of World Health Organization (WHO) underwent clinical examinations. Biochemical parameters associated with metabolic syndrome, insulin resistance (HOMA-IR) and systolic and diastolic blood pressure were also measured. A complete ophthalmologic examination was performed before the test. During the test, intraocular pressure was measured twice in the fasting state and at the first and second hours after oral glucose administration using rebound tonometry (ICARE).Results: The mean age of the 51 patients was 46.19±9.13 years. The participants were categorized as non-diabetic (n: 24) and diabetic (n: 27). The baseline glucose levels were higher in the diabetic patients (p<0.001). The first-hour intraocular pressures (IOP1-0) changes in the right eye were significant in the diabetic and non-diabetic participants, and the first-hour intraocular pressure changes in the left eye (IOP1-0l) in the diabetic group were significant (p=0.017, p=0.017, p<0.001, respectively).Conclusion: The relation between diabetes mellitus and glaucoma has been addressed in many studies, but no clear underlying mechanisms have been identified. In our study of diabetic and non-diabetic individuals, hyperglycaemia during an oral glucose tolerance test was found to be positively related to intraocular pressure, which suggests that hyperglycaemia may represent a possible mechanism by which elevated IOP occurs.
Keywords: intraocular pressure; hyperglycaemia; diabetes mellitus